2015
DOI: 10.1063/1.4927830
|View full text |Cite
|
Sign up to set email alerts
|

Studying an Agulhas ring's long-term pathway and decay with finite-time coherent sets

Abstract: Coherent sets in dynamical systems are regions in phase space that optimally "carry mass" with them under the system's evolution, so that these regions experience minimal leakage. The dominant tool for determining coherent sets is the transfer operator, which provides a complete description of Lagrangian mass transport. In this work, we combine existing transfer operator methods with a windowing scheme to study the spatial and temporal evolution of a so-called Agulhas ring: a large anticyclonic mesoscale eddy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 40 publications
2
68
1
Order By: Relevance
“…Interactions with such topographic features are not surprising given that the vertical extent of the eddies inferred from the profiles of density anomalies was deeper than 1,500 m. The loss of volume induced by such interactions is consistent with results by Frenger et al () who showed that bottom interactions are one of the most important processes to dissipate mesoscale energy in the Southern Ocean. Between the two ridges the eddies showed reduced volume losses (<0.5 × 10 13 m 3 ), as observed in Froyland et al () and Wang et al (). Other studies (Doglioli et al, ; van Sebille et al, ) have reported larger volume losses.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Interactions with such topographic features are not surprising given that the vertical extent of the eddies inferred from the profiles of density anomalies was deeper than 1,500 m. The loss of volume induced by such interactions is consistent with results by Frenger et al () who showed that bottom interactions are one of the most important processes to dissipate mesoscale energy in the Southern Ocean. Between the two ridges the eddies showed reduced volume losses (<0.5 × 10 13 m 3 ), as observed in Froyland et al () and Wang et al (). Other studies (Doglioli et al, ; van Sebille et al, ) have reported larger volume losses.…”
Section: Discussionsupporting
confidence: 75%
“…The ∼0.5 × 10 13 m 3 of water advected by eddy B12 west of 30°W corresponds to ∼33% of the initial volume of the eddy after the Mid‐Atlantic Ridge, and to ∼12.5% of the initial combined volume of eddies AN1 and AS2 east of the Walvis Ridge. These percentages are lower than those found by Froyland et al () and Wang et al (), but the difference can be mostly explained by the depth variation in eddy volume, which was not considered in those studies.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…This occurs at y =ŷ, which is the solution to sin y = −cy (33) which lies in the domain y ∈ (0, π). Equation (33) is transcendental and requires numerical evaluation.…”
Section: Formulas For Fluxmentioning
confidence: 99%
“…The formulas to be given from this point onwards assume that −1 < c < 0 (corresponding to β > 0), in which case the Rossby wave travels as in Figure 1. Having determinedŷ which satisfies (33), it is necessary to define the function…”
Section: Formulas For Fluxmentioning
confidence: 99%